Implementation Of Educational Management Functions: A Case Study At SDIT Wirausaha Indonesia - Alya Ramadhani Bangun; An-nisa Fitri Khotia Siregar; Chesia Aulia; Zhulianty Elisabeth Gultom (PT. Global Research Collaboration, 2025)
Educational management is the main key in creating a focused and quality learning process. This study aims to examine the implementation of educational management functions including planning, organizing, implementing, and supervising. Using the library study method, this article examines the literature and practices of educational management in a real context, especially through a case study at SDIT Wirausaha Indonesia. The results of the study indicate that the implementation of the four management functions in an integrated manner can increase the effectiveness of the learning process, build a positive work culture, and strengthen the involvement of all school residents.